Process evaluation of workplace health promotion in a sheltered workplace: a care ethics perspective. (14th April 2023) - van Heijster, Hanneke; van Berkel, Jantien; Bakker, Minne; Boot, Cécile; de Vet, Emely
Summary: Despite the potential health benefits of workplace health promotion for employees in sheltered workplaces, participation is often limited. The aim of this study was (i) to understand this limited participation, and (ii) to find opportunities for adapting workplace health promotion, such that it better meets the needs of the target population. A responsive process evaluation of an extensive multi-component workplace health promotion program targeting lifestyle behaviors, financial behaviors, literacy and citizenship, was performed in a large, sheltered workplace in the Netherlands (>3500 employees). To understand the limited participation, interviews with employees ( n = 8), supervisors ( n = 7) and managers ( n = 2), and 10 participant observations were performed. To find opportunities for improving workplace health promotion in the sheltered workplace, 7 dialogs with employees were performed ( n = 30). The interview data on the barriers for participation were evaluated through the lens of care ethics, as this allowed to understand the role of various stakeholders in the limited participation, as well as the indirect role of the institutional context. Findings showed that participation in workplace health promotion could increase if it is organized in a way that it encourages employees to work on health together, allow to tailor activities to different needs and capabilities of employees, and connects activities to employees' daily lives. A strength of this study is that the responsive process evaluation focused both on barriers for participation, as well as on opportunities to increase participation. Lay Summary: People who cannot participate in work without adaptations, for example, due to disability, can work in sheltered workplaces. These employees face various health risks, which are prompted by, for example, low income or low (health) literacy. More and more sheltered workplaces provide health promotion programs to improve health of their employees, such as educational workshops about physical exercise and healthy nutrition. However, participation of employees in such programs is limited. In this study, we investigated why participation is limited, and what are possible ways to make workplace health promotion programs that aim to improve health more attractive to employees in a sheltered workplace. We used different methods, such as interviews, group dialogs and participant observations. We concluded that workplace health promotion programs seem to rely too much on the individual employee, who prefers to work on health together with peers. Employees also value that activities in the health program are useful for their daily lives. This increases the relevance of the program for them and makes employees more inclined to participate.